The Consecration of the Writer Pablo Montoya Campuzano. A Glance at the Colombian Literary Institution - Mahecha Arias, Jacqueline (Universidad Pedagógica y Tecnológica de Colombia, 2018)
The first quarter of the XXIst century presents new literary dynamics linked to author consecration processes in the context of the boom of large publishing houses. In view of the above, it is necessary to understand how an author continues to struggle in order to establish his or her ideology within a system that requires specific structures for the production of thought, imagination and publications. For this purpose, we will use the theory of Jacques Dubois in order to identify the practical agents and instances within the Colombian literary institution involved in the consecration process of the writer Pablo Mon - toya, and the incidence of literary prizes that he has received